Navodila za predmet Družinska medicina II (University of Maribor Press, 2018)
Instructions for the Subject Family Medicine II. The course Family Medicine in the 6th year will be held in the lecture rooms of the Medical Faculty UM (MF), in mentoring clinics, on duty clinics, in emergency ambulances, in the patient’s home and in intervention vehicles. The training will include: seminars (30 hours + 90 hours of individual work), which will take place in the lecture room MF and individual exercises (120 hours) in family medicine clinics, which will take place according to the schedule in mentoring clinics. At the end of the lesson, the student should know the basic principles of the work of family medicine physician and acquire theoretical and practical knowledge to the intended extent. He will meet the principles of person-oriented health care and will be able to include him in the treatment of the patient to the extent necessary, he will gain knowledge of the most common clinical pictures in family medicine. He will understand that the work of a family doctor depends on the environment in which he works and that the family doctor treats the patient comprehensively, he also includes a preventive aspect and concern for his own health.